Design of a trustworthy service broker and dependence-based progressive group testing. (27th July 2007) - Bai, Xiaoying; Cao, Zhibin; Chen, Yinong
To address the challenges of dynamic, distributed and collaborative Web Services (WS) testing, this paper proposes a trustworthy service broker architecture and a dependence-based progressive group testing technique. The new architecture extends the traditional Universal Description, Discovery and Integration (UDDI) service broker by introducing the check-in and check-out testing interfaces, which are associated with a set of automated tools. The design objectives of the trustworthy service broker are to perform rigorous testing and evaluation effectively and to ensure that only quality WS can be registered and released to the public. A group testing technique is applied to reduce the test cost by using a hierarchy of increasingly sophisticated test scripts, which progressively rules out low quality WS. WS are further ranked based on the group testing results using ranking criteria. Experiments show that this approach can effectively test and choose WS in an open environment and in reduced number of tests.